2009
DOI: 10.1348/135910708x336112
|View full text |Cite
|
Sign up to set email alerts
|

Using an extended theory of planned behaviour to inform interventions aimed at increasing breastfeeding uptake in primiparas experiencing material deprivation

Abstract: The TPB provided a useful framework with which to examine the factors underlying breastfeeding intentions and behaviour amongst primiparas. A grouping system based on the congruence between intentions and subsequent behaviour revealed important differences between beliefs of the three groups. Further research might usefully test the effectiveness of interventions targeting the beliefs identified here in increasing breastfeeding uptake and duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 40 publications
2
53
1
1
Order By: Relevance
“…Pro‐breastfeeding descriptive norms have been shown to be important in the prediction of breastfeeding at 10 days (McMillan et al ., 2009), but this study showed that vicarious experience may act in the formation of social cognitions such as attitudes. Vicarious experience of formula‐feeding was associated directly with behaviour; those mothers with more vicarious experience of formula‐feeding were less likely to be breastfeeding at 6–8 weeks regardless of their own personal experience.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Pro‐breastfeeding descriptive norms have been shown to be important in the prediction of breastfeeding at 10 days (McMillan et al ., 2009), but this study showed that vicarious experience may act in the formation of social cognitions such as attitudes. Vicarious experience of formula‐feeding was associated directly with behaviour; those mothers with more vicarious experience of formula‐feeding were less likely to be breastfeeding at 6–8 weeks regardless of their own personal experience.…”
Section: Discussionmentioning
confidence: 59%
“…However, even in this sample there was a considerable reduction in the rate of breastfeeding in the first 6 weeks (from 99% to 79%), and identifying the important factors associated with those who continue or stop breastfeeding by this stage is important. Furthermore, where the variables and analyses were similar to previous studies, the findings were also similar – even when compared to a deprived sample (McMillan et al ., 2008, 2009). This suggests that many of the factors associated with infant feeding, and in particular the relative importance of past experience and self‐efficacy, may be similar across socio‐economic groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in relation to breastfeeding, McMillan et al (33) reported the direct effects for education and household deprivation on behavior to be partially mediated by TPB variables. Similarly, in relation to physical activity, Godin et al (5) reported the direct effects for education and income on behavior to be partially mediated by TPB variables.…”
Section: Ses and The Health Cognition-behavior Relationshipmentioning
confidence: 99%
“…There are defined limits on the generalisability of findings from qualitative studies 19 In the UK teenage mothers are among the least likely to breastfeed 1 . Studies have been carried out into the reasons why those from disadvantaged groups do not initiate and continue breastfeeding, many of which are linked to the theory of planned behaviour 10,11,20 . Such studies conclude that family influences and concerns about breastfeeding in public significantly influence infant feeding behaviour 20 and that breastfeeding can be seen as a 'morally inappropriate' behaviour by teenagers 11 .…”
Section: Limitations Of This Studymentioning
confidence: 99%